Effecf of processing on the protein quality and the texture profile of canned terrestrial snail achatina fulica / Mohd Irwani Hafiz Sahid - Hafiz Sahid, Mohd Irwani (2007)
The edible terrestrial snail, Achatina fulica is at present under utilised in Malaysia. It is not consumed because of the stigma of it being classified as a pest. The aim of this work is to evaluate the nutritional and textural quality and changes of the meat of Achatina fulica under different processing conditions, namely, the brine concentration (1-4%) and sterilisation time (30 and 45 minutes at 121.1°C). Physicochemical analysis (proximate analysis , mineral content, pH, caloric value), changes in protein and the amino acid content before and after processing , canning medium analysis for presence of amino acids, and texture evaluation were conducted. Physico-chemical analyses were determined using well-established methods, amino acid content were determ ined by the AccQ.Tag Method, while texture determination (TPA) was conducted using the TA-XT2 texture analyser. The proximate analysis conducted in this study reveals that the meat of Malaysia's wild Achatinafulica is nutritious. It is high in protein , at 11.30% (raw). It contains all the essential amino acids . It is also high in calcium (0.24%), low in fat (1.25%) and caloric value (99.75kcal), with neutral pH (7.38). The change of protein content of the meat of Achatina fuli ca canned at different brine concentrations and sterilisation times were minimal, showing significant difference for brine concentration of 4% at 30 minutes sterilisation time and all range of salt concentrations at 45 minutes sterilisation time (p<0.05). Changes in amino acid content were also minimal , with significant differences observed for Histidine, Lysine, Methionine, Tryptophan, Arginine , Isoleucine, and Leucine. However, loss of Histidine, Lysine, Methionine and tryptophan were observed in all treatments. Canning medium analysis showed presence of amino acids , suggesting that solubilisation of prote in is one mechanism that caus~ the reduction of protein content during canning. However, the loss was not significant (P<0.05). The texture profile analysis of the meat of Achatina fulica canned at different processing condition showed some changes within the experimental treatments , however, these were not significantly different (P<0.05) .